Endoscopic submucosal dissection assisted by adaptive traction: results of the first 54 procedures - Masgnaux, Louis-Jean; Grimaldi, Jean; Rivory, Jérôme; Ponchon, Thierry; Yzet, Clara; Wallenhorst, Timothée; Lupu, Alexandru; Lafeuille, Pierre; Legros, Romain; Rostain, Florian; Jacques, Jérémie; Pioche, Mathieu (Endoscopy, 2023)
Background Good submucosal exposure is key to successful endoscopic submucosal dissection (ESD) and can be achieved with various traction devices. Nevertheless, these devices have a fixed traction force that tends to decrease as the dissection progresses. In contrast, the ATRACT adaptive traction device increases traction during the procedure.Methods In this retrospective analysis of prospectively collected data (from a French database), we analyzed ESD procedures performed with the ATRACT device between April 2022 and October 2022. The device was used consecutively whenever possible. We collected details of lesion characteristics, procedural data, histologic outcomes, and clinical consequences for the patient.Results 54 resections performed in 52 patients by two experienced operators (46 procedures) and six novices (eight procedures) were analyzed. The ATRACT devices used were the ATRACT-2 (n = 21), the ATRACT 2 + 2 (n = 30), and the ATRACT-4 (n = 3). Four adverse events were observed: one perforation (1.9 %), which was closed endoscopically, and three delayed bleeding events (5.5 %). The R0 rate was 93 %, resulting in curative resection in 91 % of cases.Conclusion ESD using the ATRACT device is safe and effective in the colon and rectum, but can also be used to assist with procedures in the upper gastrointestinal tract. It may be particularly useful in difficult locations.